AEROMYCOLOGICAL STUDIES OF INDOOR ENVIRONMENT OF RAMDEOBABA SOLVENT, BRAMHAPURI DIST.CHANDRAPUR (MAHARASHTRA) INDIA - SHANKAR G. KUKREJA,; ANKUSH L. MISAR,; ARVIND J. MUNGOLE, (The Bioscan, 2025)
The aim of this study was to determine the fungal spore concentration in indoor environment of Ramdeobaba solvent, Bramhapuri dist. Chandrapur (Maharashtra) India and identification of dominant genera. Indoor environment having organic substrate contains more concentration of fungal propagules as compared to outdoor environment. This fungal concentration varies by meteorological parameters like temperature and humidity. the present study air samples were collected from February 2023 to January 2024 by petriplate method and Hi air sampler method. The dominant genera of fungi found in Ramdeobaba Solvent were Rhizopus, Mucor, Alternaria, Aspergillus, Penicillium, Chaetomium, Cladosporium, Curvularia and Fusarium. Maximum fungal spore concentration was found in month of August at preparation section while minimum concentration was month May at refinery section. Comparatively the fungal spore concentration varied according to meteorological condition of every month availability of substrate at indoor places.